2021
DOI: 10.1002/hep.31718
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Cyanoacrylate Injection Versus Balloon‐Occluded Retrograde Transvenous Obliteration for Prevention of Gastric Variceal Bleeding: A Randomized Controlled Trial

Abstract: Background and Aims The optimal treatment for gastric varices (GVs) is a topic that remains open for study. This study compared the efficacy and safety of endoscopic cyanoacrylate injection and balloon‐occluded retrograde transvenous obliteration (BRTO) to prevent rebleeding in patients with cirrhosis and GVs after primary hemostasis. Approach and Results Patients with cirrhosis and history of bleeding from gastroesophageal varices type 2 or isolated gastric varices type 1 were randomized to cyanoacrylate inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 36 publications
5
56
0
1
Order By: Relevance
“…A very recent study was the first randomized controlled trial to demonstrate the superiority of BRTO in the management of (re)bleeding from GVs. In this study, Luo and colleagues found that BRTO as the therapeutic modality for bleeding GVs resulted in fewer hospitalizations, in-patient stays, and lower medical costs [ 83 ].…”
Section: Types Of Shunts and Their Reported Clinical Associationsmentioning
confidence: 99%
“…A very recent study was the first randomized controlled trial to demonstrate the superiority of BRTO in the management of (re)bleeding from GVs. In this study, Luo and colleagues found that BRTO as the therapeutic modality for bleeding GVs resulted in fewer hospitalizations, in-patient stays, and lower medical costs [ 83 ].…”
Section: Types Of Shunts and Their Reported Clinical Associationsmentioning
confidence: 99%
“…BRTO is currently recognized as an alternative to TIPS for treatment of fundal varices associated with a large gastro/splenorenal collateral when the patient is not an appropriate candidate for TIPS because of hepatic encephalopathy or poor hepatic reserve [ 15 , 79 ]. A recent trial showed that BRTO was more effective than endoscopic cyanoacrylate injection in preventing rebleeding from gastric variceal bleeding [ 80 ]. During the BRTO procedure, sclerosing agents, such as ethanolamine oleate or sodium tetradecyl sulfate mixed with water-soluble contrast media or Lipiodol ® , are used for gastric varix obturation [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the recent article (1) comparing endoscopic cyanoacrylate injection to balloon retrograde transvenous obliteration (BRTO) for the prevention of bleeding in patients with cirrhosis and gastric varices (GV) after primary hemostasis. The authors conclude that BRTO for secondary prophylaxis resulted in a lower risk of rebleeding compared to cyanoacrylate injection.…”
Section: To the Editormentioning
confidence: 99%